2020
DOI: 10.1016/j.ejca.2020.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Older versus younger adults with gastric cancer receiving perioperative treatment: Results from the CRITICS trial

Abstract: To evaluate treatment-related toxicity, treatment compliance, surgical complications and event-free survival (EFS) in older (70 years) versus younger (<70 years) adults who underwent perioperative treatment for gastric cancer. Methods: In the CRITICS trial, 788 patients with resectable gastric cancer were randomised before start of any treatment and received preoperative chemotherapy (3 cycles of epirubicin, cisplatin or oxaliplatin and capecitabine), followed by surgery, followed by either postoperative chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In contrast, a pooled analysis concluded that chemotherapy-related serious adverse events were significantly higher in > 65 year-old patients [65]. Accordingly, a recent study demonstrated that older GC patients (≥ 70) experience more severe toxicities versus younger patients [66]. A number of studies, including meta-analyses, have shown an increased risk of severe toxicity associated to fluoropyrimidine/platinum-based chemotherapy in female gastric and colorectal cancer patients [7,36,37,67].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a pooled analysis concluded that chemotherapy-related serious adverse events were significantly higher in > 65 year-old patients [65]. Accordingly, a recent study demonstrated that older GC patients (≥ 70) experience more severe toxicities versus younger patients [66]. A number of studies, including meta-analyses, have shown an increased risk of severe toxicity associated to fluoropyrimidine/platinum-based chemotherapy in female gastric and colorectal cancer patients [7,36,37,67].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, perioperative treatment compliance, especially in the postoperative phase, was poorer in older adults when compared with younger. 28 This may be one of the reasons why older age is associated with worse cancer-specific mortality in the perioperative therapy setting that is recommended in Europe.…”
Section: Elderlymentioning
confidence: 99%
“…In fact, we demonstrated that the difference in complication rate between NAT and US group is relevant over 60 years old ( p = 0.013) but not in younger patients ( p = 0.620). Although it has been previously demonstrated that age is a significant predictor of postoperative complications, 42–44 it is still controversial if NAT could negatively affect short‐term outcomes in older patients as reported by Fujitani et al 45 or not 46 …”
Section: Discussionmentioning
confidence: 99%